The Role of Parents in Early Childhood Character Building in Bontoala Village, Pallangga District, Gowa Regency - Nur, Asma; Malli, Rusli (Universitas Dharmawangsa Medan, 2024)
Parents play a very important role in the process of forming children's character, the formation process carried out by parents is to focus on seeing how the child's condition and understanding their nature then parents are present to carry out their role of providing examples for children and being a good example. Early childhood character building in Bontoala Village, Pallangga District, Gowa Regency is quite good. Because looking at some of the children's characters, there are some that are really paid attention to by their parents, and there are also some others that are less noticed, ranging from habits at home and who their friends hang out with outside the home. And the supporting factors of parents in the formation of children's character are adequate facilities and infrastructure, a good environment, and support from the family. Meanwhile, the inhibiting factors in the formation of children's character are television broadcasts and excessive use of mobile phones, children's pleasure in playing, busy parents, and the environment of friends.